Students’ perceptions of using SemMinder English Planner in language learning / Soo Yew Phong...[et.al] - Phong, Soo Yew; Kamarudin, Nur Asyikeen; Hamzah, Fazlinda; Sharifudin, Mohd Azlan Shah (Universiti Teknologi MARA, Cawangan Melaka, 2017)
The use of traditional notebook remains relevant among students despite there being numerous kinds of planners and writing pads sold on the market to cater the needs of consumers today. For some, the experience of using a notebook cannot be traded with the use of writing gadgets. Using notebooks also could assist with individual learnings as using appropriate supplemental materials and methods to organize and present only relevant information is thought to be able to increase the efficiency of the self-learning process (Ruiji, 2012). With literature on notebooks as the basis, this paper is attempting to extend the concept to the use of planner for class. The purpose of this paper is to study students’ perceptions of SemMinder English Planner (SEP) as a personalized planner in language learning. This paper also opens up a way for educators to incorporate their current lessons and materials into a personalized planner to increase students’ motivation and achievement.